2019
DOI: 10.1016/j.bbrc.2019.02.095
|View full text |Cite
|
Sign up to set email alerts
|

CDDO-Me, Sulforaphane and tBHQ attenuate the RANKL-induced osteoclast differentiation via activating the NRF2-mediated antioxidant response

Abstract: Metabolic bone diseases are global public health concerns and are primarily caused by uncontrolled osteoclast (OC) formation and activation. During OC differentiation, intracellular reactive oxygen species (ROS) stimulated by receptor activator of nuclear factor kappa-B ligand (RANKL) can serve as the signaling molecules to promote osteoclastic genes expression. Nuclear factor erythroid-2 related factor 2 (NRF2), a master mediator of cellular antioxidant response, also plays a critical role in OC differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…However, TBHQ as an activator of ERK did not aggravate DSS-induced colitis. It may be that TBHQ can also activate nuclear factor erythroid-2 related factor 2 (Nrf2)-mediated antioxidant response, which may partially neutralize the colonic damage caused by the activation of the ERK pathway ( Xue et al, 2019 ). In vitro , BTW also inhibited the activity of NF-κB/ERK in LPS-activated RAW 264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, TBHQ as an activator of ERK did not aggravate DSS-induced colitis. It may be that TBHQ can also activate nuclear factor erythroid-2 related factor 2 (Nrf2)-mediated antioxidant response, which may partially neutralize the colonic damage caused by the activation of the ERK pathway ( Xue et al, 2019 ). In vitro , BTW also inhibited the activity of NF-κB/ERK in LPS-activated RAW 264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that SFN could also be used to treat diseases associated with pathological bone resorption, such as bone metastasis in breast cancer, osteoporosis, and osteoarthritis [ 25 , 26 , 27 ]. In addition, Tomohiro Takagi et al suggested that SFN plays a negative role in RANKL-induced osteoclastogenesis, but the underlying mechanisms need to be further investigated [ 10 , 28 ]. Autophagy is required during osteoclastogenesis and could be modulated by SFN.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of matrix metalloproteinases-2/-9, primary effects of triterpenoids on their activity, as far as we know, have not been yet published, however, recently, Preciado et al reported that betulinic, oleanolic and ursolic acids can bind to catalytic site of snake venom metalloproteinases, being similar to those in human matrix metalloproteinases, and significantly inhibit their enzymatic and biological activities [ 93 , 94 ]. Furthermore, CDDO-Me and its analog RTA408 were found to decrease expression of MMP-9 in various models, including tumor necrosis factor α- (TNF-α-), receptor activator of nuclear factor kappa-B ligand- (RANKL-) and interleukin 1β- (IL-1β)-stimulated chronic myelogenous leukemia KBM-5 cells, RAW264.7 macrophages and rat brain astrocytes [ 72 , 95 , 96 ], respectively, as well as primary mammary tumor cells, isolated from polyoma middle T mice [ 97 ], which is consistent with revealed ability of SM to inhibit expression of MMP-9 in metastatic foci in lungs of B16 melanoma-bearing mice ( Figure 8 E). It should be emphasized, however, that prediction of JNK1 and MMP-2/-9 as EMT-associated protein targets of SM was carried out using computer modeling approach and, therefore, these findings only hypothesize about probable molecular mechanism of inhibitory effect of SM on EMT.…”
Section: Discussionmentioning
confidence: 99%